(untitled) (Research, Society and Development, 2021)
The empirical-inductivist paradigm of science was important for humanity to experience a rapid expansion of its horizons of knowledge. However, over time, this way of conceiving scientific work led individuals to establish mistaken and simplistic beliefs about scientific work and the role of science. From this perspective, the overcoming of distorted views of science by social individuals permeates the understanding, analysis and critical reflection of the external conditions that have guided scientific and technological development so far. Therefore, this manuscript aims, through a theoretical and reflective study, to conjecture about the history, foundations and evolution of scientific knowledge. We will start our journey through the Modern Age, where we will seek to highlight the characteristics and differences between the dominant philosophical currents that followed until the mid-nineteenth century. Next, we will enter the 20th century, where we will highlight the contributions of some of the main contemporary philosophers who, through their theories, sought to establish a more critical view of the production of scientific knowledge and the role of Science. Finally, we will address the contributions of a possible association between STS education and History and Philosophy of Science (HFC), as an approach to science teaching capable of contemplating the historical and philosophical dimension of scientific knowledge, considering its social implications, cultural, technological and political.